2007
DOI: 10.1111/j.1442-9071.2007.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding characteristics of a new hydrophobic acrylic intraocular lens, and possible association with complications in triple procedures

Abstract: Incomplete unfolding of the VA60BB appears to cause intraoperative rotation of the IOL in the capsular bag, resulting in IOL dislocation into the vitreous cavity in the presence of a posterior capsular hole. This lens also appears to be associated with higher rate of postoperative complications in triple procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Iwase and Tanaka reported that incomplete unfolding of the hydrophobic acrylic Hoya AF-I caused intraoperative rotation of the IOL in the capsular bag. The tendency of the unfolding and rotation can result in optical rotation and potential contact with the endothelium or inverted implantation (the implant positioned upside down) [ 16 , 17 ]. Decreased implantation time could reduce the risk of complications arising from incomplete IOL unfolding.…”
Section: Discussionmentioning
confidence: 99%
“…Iwase and Tanaka reported that incomplete unfolding of the hydrophobic acrylic Hoya AF-I caused intraoperative rotation of the IOL in the capsular bag. The tendency of the unfolding and rotation can result in optical rotation and potential contact with the endothelium or inverted implantation (the implant positioned upside down) [ 16 , 17 ]. Decreased implantation time could reduce the risk of complications arising from incomplete IOL unfolding.…”
Section: Discussionmentioning
confidence: 99%
“…Further, extended unfurling time prevents effective IOL fixation, leading to rotation of the IOL and even dislocation into the vitreous cavity. 3 Predictable unfurling is vital during the implantation of toric IOLs, when precise alignment of the optic is needed to restore optimal vision. 4 , 5 Thus, parameters surrounding IOL unfurling represent an important clinical interest to minimize surgical time and operative costs while improving clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%